Relationship of Phosphatidylethanol Biomarker to Self‐Reported Alcohol Drinking Patterns in Older and Middle‐Age Adults. (9th November 2020) - Cherrier, Monique M.; Shireman, Laura M.; Wicklander, Katie; Yeung, Winnie; Kooner, Preetma; Saxon, Andrew J.; Simpson, Tracy; Terman, Greg; Shen, Danny
Abstract : Background: Risky alcohol consumption is on the rise among older adults. Biomarkers such as phosphatidylethanol (PEth) have been used to evaluate the correspondence between an objective, laboratory‐based biomarker and self‐report of alcohol consumption. This study examined the relationship between PEth, self‐report of alcohol consumption, and health indices in a sample of community‐dwelling older to middle‐age adults (aged 35 to 89) with healthy and risky levels of alcohol consumption. Methods: Self‐reports of alcohol consumption were collected using the Alcohol Use Disorders Identification Test (AUDIT) and Form 30. In addition, indices of health along with a blood sample to determine PEth values were collected ( N = 183). Results: PEth was correlated with age, AUDIT‐C, AUDIT total, alcohol consumption, mood, and liver function measures but not with medical comorbidity or body mass index (J Gerontol B Psychol Sci Soc Sci 73, 2018, 633). Alcohol consumption over the past 30 days measured with Form 30 was the strongest predictor of PEth levels for both middle‐age and older adults, with age a small contributing predictor. General alcohol consumption patterns for amount of alcohol consumed over a 30‐day period revealed middle‐age adults consumed larger amounts of alcohol compared with older adults, but older adults consumed alcohol on more days than middle‐age adults. Middle‐age participants evidenced higher PEth levels than older adults at comparable drinking rates. Conclusions: Overall, findings suggest a strong relationship between alcohol consumption and PEth levels with age a small but contributing factor to predicting PEth levels. Abstract : Unhealthy alcohol consumption is on the rise in older adults. A sample of middle age and older adults (age 35–89 years) found middle age adults consumed more drinks over thirty days (Form ‐30), whereas older adults consumed alcohol over more days (Form‐30). Alcoholic drinks consumed over 30 days was a strong predictor of phosphatidylethinol (PEth) (above left) with age a contributing factor (above right).